Synthesis and Mesophase Behavior of Phenylthiophene Based Amphiphilic Molecules - 经山 张瑞林 戴衡 杜超 程晓红 (Chinese journal of chemistry, 2012)
Novel amphiphilic molecules consisting of a rigid 2-phenylthiophene core, with a polar flexible tri（oxylethylene） moiety attached to the phenyl ring and one or two alkyl chains attached to the thiophene ring at the other side have been synthesized by using Ni（II） and Pd（0） catalyzed coupling reaction as key steps. The tri（oxylethylene） moieties were terminated with hydroxyl group, sodium carboxylate group and lithium carboxylate group respectively. The thermotropic and solvent induced liquid crystalline behavior of these substances was investigated by polarized op- tical microscopy, differential scanning calorimetry and X-ray diffraction. Thereby the influence of the terminal groups attached to the tri（oxylethylene） moities as well as the influence of the length and the number of the alkyl chains on the mesophase behavior were investigated. The single alkyl chain Na-carboxylate termianted derivatives show smectic A phases, double alkyl chain Na-carboxylate terminated derivatives show a thermo tropic hexagonal columnar mesophase, while columnar mesophases are found in both single and double alkyl chain Li-carbonate terminated derivatives. The model for molecular organization in the hexagonal columnar mesophase is established,